THE ROLE OF THE SHARIA SUPERVISORY BOARD IN MURABAHAH FINANCING: In The Mitra Niaga Sejahtera - Eriyanti, Nahara; Salsabila, Tiara; Khalidi, Muhadi (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2024)
One of the financial institutions that contributes effectively to channeling business capital financing in the Aceh Besar area is the Mitra Niaga Sejahtera Sharia Consumer Cooperative. This institution is supervised by the Sharia Supervisory Board which is tasked with supervising the operations and practices of LKS so that it adheres strictly to sharia principles. This article examines the murabahah financing mechanism and analyzes the extent of supervision by the Sharia Supervisory Board at the Mitra Niaga Sejahtera Sharia Consumer Cooperative regarding the financing mechanism. The research method used is qualitative research and produces data in the form of descriptive analysis. Data collection techniques use field interview techniques and documentation. The results of the author's analysis show that the initial mechanism for becoming a member/potential member of murabahah financing is by submitting an application for murabahah business capital financing with predetermined conditions, ensuring that the murabahah financing meets the target, carrying out inspections of pillars such as contracts, transacting parties, The object, purpose and benefits of the financing and the form of supervision carried out by the DPS regarding murabahah financing is conducting visits to cooperatives to check the correctness of the contracts, objects and accurate evidence, and ensuring procedures or Standard Operating Procedures (SOP) are in accordance with sharia rules. The supervisory practices carried out by DPS regarding murabahah financing in this cooperative are in accordance with the applicable supervisory mechanism because it assesses all forms of practices carried out in accordance with the applicable SOP and established by DSN as a reference. This research offers the role of DPS in each sharia financial institution after the implementation of Qanun Aceh No. 11 of 2018 concerning Sharia Financial Institutions